Contributions of precision engineering to the revision of the SI. Issue 2 (2017) - Bosse, Harald; Kunzmann, Horst; Pratt, Jon R.; Schlamminger, Stephan; Robinson, Ian; de Podesta, Michael; Shore, Paul; Balsamo, Alessandro; Morantz, Paul
Abstract: All measurements performed in science and industry are based on the International System of Units, the SI. It has been proposed to revise the SI following an approach which was implemented for the redefinition of the unit of length, the metre, namely to define the SI units by fixing the numerical values of so-called defining constants, including c, h, e, k and N A . We will discuss the reasoning behind the revision, which will likely be put into force in 2018. Precision engineering was crucial to achieve the required small measurement uncertainties and agreement of measurement results for the defining constants.